2021
DOI: 10.1161/circulationaha.120.050682
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21–Dependent Macrophage-to-Fibroblast Signaling Determines the Cardiac Response to Pressure Overload

Abstract: Background: Cardiac macrophages (cMP) are increasingly recognized as important regulators of myocardial homeostasis and disease, yet the role of noncoding RNA in these cells is largely unknown. Small RNA sequencing of the entire miRNomes of the major cardiac cell fractions revealed microRNA-21 (miR-21) as the single highest expressed microRNA in cMPs, both in health and disease (25% and 43% of all microRNA reads respectively). MiR-21 has been previously reported as a key microRNA driving tissue fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 64 publications
(41 reference statements)
0
71
0
Order By: Relevance
“…The activation of cardiac fibroblasts could also be suppressed by macrophage-specific deletion of microRNA-21 which decreased interstitial fibrosis in mice following pressure overload ( Ramanujam et al, 2021 ). Deletion of microRNA-21 in macrophages increased M2-polarized macrophages, while decreased M1-like proinflammatory macrophages which might disrupted the macrophage-to-fibroblast signaling and activation of cardiac fibroblasts ( Table 1 ) ( Ramanujam et al, 2021 ).…”
Section: Targeting Activated Cardiac Fibroblasts For Anti-fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of cardiac fibroblasts could also be suppressed by macrophage-specific deletion of microRNA-21 which decreased interstitial fibrosis in mice following pressure overload ( Ramanujam et al, 2021 ). Deletion of microRNA-21 in macrophages increased M2-polarized macrophages, while decreased M1-like proinflammatory macrophages which might disrupted the macrophage-to-fibroblast signaling and activation of cardiac fibroblasts ( Table 1 ) ( Ramanujam et al, 2021 ).…”
Section: Targeting Activated Cardiac Fibroblasts For Anti-fibrosismentioning
confidence: 99%
“…The activation of cardiac fibroblasts could also be suppressed by macrophage-specific deletion of microRNA-21 which decreased interstitial fibrosis in mice following pressure overload ( Ramanujam et al, 2021 ). Deletion of microRNA-21 in macrophages increased M2-polarized macrophages, while decreased M1-like proinflammatory macrophages which might disrupted the macrophage-to-fibroblast signaling and activation of cardiac fibroblasts ( Table 1 ) ( Ramanujam et al, 2021 ). However, during the proliferative phase of MI, CD226 deletion also increased M2-macrophages and decreased M1-macrophages, but it resulted in accumulation of myofibroblasts and collagen deposition in the infarct area, with reduced interstitial fibrosis in the infarct border area though ( Li et al, 2020 ).…”
Section: Targeting Activated Cardiac Fibroblasts For Anti-fibrosismentioning
confidence: 99%
“…This may be because multiple pathways lead to activation of fibroblasts and different macrophage populations might use distinct pathways especially in the context of the method used to induce PO, i.e., Ang II versus transverse aortic constriction (TAC). For example, using TAC, a murine model of PO, expression of microRNA-21 (mir-21) in macrophages was shown to induce a pro-inflammatory macrophage phenotype [ 45 ]. Furthermore, mice with deleted macrophage expression of miR-21 demonstrated reduced fibrosis and fewer myofibroblasts suggesting that pro-inflammatory macrophages were primary drivers of fibrosis [ 45 ].…”
Section: Immune Cell Heterogeneity In the Heartmentioning
confidence: 99%
“…For example, using TAC, a murine model of PO, expression of microRNA-21 (mir-21) in macrophages was shown to induce a pro-inflammatory macrophage phenotype [ 45 ]. Furthermore, mice with deleted macrophage expression of miR-21 demonstrated reduced fibrosis and fewer myofibroblasts suggesting that pro-inflammatory macrophages were primary drivers of fibrosis [ 45 ]. In another model of PO using Ang II infusion, Falkenham et al demonstrated that depletion of macrophages using clodronate liposomes reduced levels of αSMA+ myofibroblasts, decreased collagen content, and decreased levels of mRNA encoding Cxcl3 , a nonclassical macrophage marker supporting an essential role of non-classical macrophages in fibrosis.…”
Section: Immune Cell Heterogeneity In the Heartmentioning
confidence: 99%
“…Ramanujam et al applied ligand–receptor pair analysis to scRNA-seq data from non-CMs in pressure-overloaded murine hearts by analyzing the transcripts of secreted protein ligands in one cell type and their receptors in another cell type, and predicted that M1 like macrophages interacted with activated fibroblasts via secreted proteins such as TGFβ and fibronectin. These interactions were demonstrated to be mediated by macrophage miR-21, depletion of which rescued hypertrophic phenotype after TAC ( 76 ). Martini et al, by sequencing cardiac CD45 + cells, showed increases in Osm + pro-inflammatory macrophages, as well as Pdcd 1 + Tregs, in pressure-overloaded murine hearts when compared with healthy hearts ( 77 ).…”
Section: Heart Failure and Miscellaneousmentioning
confidence: 99%